Efeito farmacológico da friedelina livre e complexada em hidroxipropil-β-ciclodextrina em modelos de inflamação em roedores - Ferro, Jamylle Nunes de Souza (2016)
Natural products are commonly used for the treatment of different pathologies, including inflammation. Among the molecules present in plants, the triterpenes exibith wide range of pharmacological effects, including anti-inflammatory and antioxidant actions. In the present study were sought to investigate the effect of friedelin at the inflammatory response in vivo. The study also looked to characterize the formation of inclusion complex between friedelin and hydroxypropyl-β-cyclodextrin, and to evaluate its potential to inhibit allergic inflammation in experimental asthma model mice. Initially, were demonstrated that friedelin is able to inhibit the plasma extravasation at the edema model induced by carrageenan, histamine and PGE2, but not by serotonin. Then, with the purpose of evaluating with the actions of friedelin extend on the cellular events of inflammation; we assessed the effect of this triterpene on the inflammatory response induced by LPS using the pleurisy model. In this experimental model, friedelin inhibited the influx of neutrophils as well as the amount of cytokines and inflammatory chemokines in the pleural effluent. Furthermore, in assessing the effect of friedelin on mobilization of human neutrophils, were demonstrated, in vitro, that friedelin induced in a lower adherence of neutrophils to activated endothelium, as well as a lower chemotactic response which were not associated with reduction in viability. These results suggest a direct effect of friedelin in neutrophils. Subsequently, to confirm whether these effects would be also observed in vivo, were decided to evaluate leukocyte motility events using intravital microscopy. In this model, we confirmed that friedelin was able of reducing rolling and adhesion of leukocytes, events that can be associated with lower influx of leukocytes to the inflammatory site. Additionally, we confirmed that friedelin allowed be attached to cyclodextrin, phenomenon that was demonstrated by using spectroscopic methods, such as analysis by ultraviolet-visible and infrared. Moreover, the effects of friedelin and its complex with cyclodextrin were evaluated against allergic pulmonary inflammation induced by ovalbumin. In this experimental model, both friedelin and friedelin:cyclodextrin inhibited the parameters of respiratory mechanics as resistance and airway elastance. We also verify that both leukocyte recruitment and the production of cytokines and chemokines in bronchoalveolar lavage were inhibited by the treatment with friedelin and friedelin:cyclodextrin. Additionally, treatment with friedelin:cyclodextrin increased the amount of cytokine IL-10 in bronchoalveolar lavage. Evaluation of lung tissue from asthmatic animals we noted that several histopathological changes, such as extracellular matrix deposition and mucus production, were also inhibited under friedelin and friedelin:cyclodextrin treatments. These treatments also restored the activity of catalase in lung from asthmatic animals. In conclusion, the data obtained in this study shows that the carrier system of friedelin with hydroxypropyl-beta-cyclodextrin increases the anti-inflammatory effects of friedelin in preventing the onset of inflammation in acute asthma.